The fundamental karyotype and plastid DNA of Alstroemeria piperata (Liliales, Alstroemeriaceae), a species endemic to the Valparaíso Region, Chile - Perry, Carlos Baeza; Rojas, Gloria; Toro-Núñez, Óscar; Ruiz-Ponce, Eduardo (Phytotaxa, 2023)
A recently described species of Chilean Alstroemeria, A. piperata, is endemic to the Mediterranean region and characterized by having storage roots covered with whitish hairs. It is a highly endangered species, consisting only of a single population with few individuals. Its chromosomes are 2n = 16, typical for the genus, but they possess unique secondary constrictions. A molecular analysis of plastid DNA revealed no single nucleotide polymorphisms, which suggests that processes of phenotypic stabilization and incipient genetic isolation may be occurring within the species.